Pathological Findings in Chest Radiographs of Chronic Kidney Disease Patients Undergoing Hemodialysis - Siti Nurhayati Utami; Hanna Marsinta Uli; Indri Seta Septadina (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Chronic kidney disease is a condition in which there is destruction of the kidneys along with structural or functional abnormalities, with or without decreased glomerular filtration rate for more than 3 months. The common treatment for this condition is hemodialysis, however, it may cause complications, specifically cardiovascular and non-cardiovascular system dysfunctions that can be observed through thorax imaging. This study aims to observe pathologic thorax imaging findings on chronic kidney disease patients undergoing hemodialysis at RSUP Dr. Mohammad Hoesin Palembang. This study is a descriptive study using a cross-sectional design. The data is gathered from medical records from the Medical Records & Radiology Department of RSUP Dr. Mohammad Hoesin Palembang that have passed the inclusion and exclusion criteria. The data is processed using the SPSS application version 25. The results of this study indicate that, based on risk factors, patients are generally in the 55-64 age range (41%), female (60%), and with a normal BMI/normal weight (52%). Based on the patients’ comorbid diseases, patients mostly have hypertension (59%), followed by diabetes mellitus (46%). Analysis of the chest radiographs indicate that (70%) of patients have cardiomegaly; (22%) of patients have grade 1, (15%) have grade 2, (7%) have grade 3 aortic arch calcification; (49%) have pulmonary edema; (31%) have unilateral pleural effusion, and (14%) have bilateral pleural effusion. The majority of chronic kidney disease patients undergoing hemodialysis at RSUP Dr. Mohammad Hoesin Palembang are in the 55-64 age range, female, and with normal BMI. The most common comorbid conditions are hypertension and diabetes mellitus. Analysis of the chest radiographs indicate that the majority of patients have cardiomegaly; grade 1, 2, and 3 aortic arch calcification; pulmonary edema; unilateral and bilateral pleural effusion.